Advances in Intergroup Contact. - Hodson, Gordon (Taylor and Francis, 2012)
Intergroup contact remains one of the most effective means to reduce prejudice and conflict between groups. The past decade has witnessed a dramatic resurgence of interest in this time-tested phenomenon, with researchers now focusing on understanding when, why, and for whom contact does (and does not) work. This new volume focuses on one of the hottest topics in the social sciences: prejudice. Covering not only basic principles but cutting-edge findings and theoretical directions, key questions surrounding this subject are addressed, such as:how perceptions of other groups lead to anxiety and.